2016
DOI: 10.1002/biot.201600015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and retargeting transcriptional hot spots in the human genome

Abstract: Mammalian cell line development requires streamlined methodologies that will reduce both the cost and time to identify candidate cell lines. Improvements in site-specific genomic editing techniques can result in flexible, predictable, and robust cell line engineering. However, an outstanding question in the field is the specific site of integration. Here, we seek to identify productive loci within the human genome that will result in stable, high expression of heterologous DNA. Using an unbiased, random integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 63 publications
1
15
0
1
Order By: Relevance
“…Interestingly, 20/21 integration sites are found in non-coding regions or gene introns. Similar enrichment of non-coding and intronic regions was observed in transcriptional hot spots in the human genome ( 43 ). Future analysis of a larger set of stable integration sites may help elucidate genomic features that make certain loci better LPs and could also lead to better criteria for identifying prospective stable integration sites in mammalian cells.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, 20/21 integration sites are found in non-coding regions or gene introns. Similar enrichment of non-coding and intronic regions was observed in transcriptional hot spots in the human genome ( 43 ). Future analysis of a larger set of stable integration sites may help elucidate genomic features that make certain loci better LPs and could also lead to better criteria for identifying prospective stable integration sites in mammalian cells.…”
Section: Discussionsupporting
confidence: 63%
“…This suggested that they might contain integration events or arrangements that bypass silencing mechanisms. These transformants could provide empirical evidence for putative safe-harbour loci, which have been previously verified in various other organisms including mammalian cell lines (Lee et al, 2015;Cheng et al, 2016;Papapetrou and Schambach, 2016;Salsman and Dellaire, 2016), rice (Cantos et al, 2014) and cyanobacteria (Bentley et al, 2014;Pinto et al, 2015).…”
Section: Rice Cell Lines Exhibit Dramatically Varied Stability That Dmentioning
confidence: 56%
“…Targeted gene integration can improve transgene expression levels when appropriate integration locations are selected; namely, regions that permit insertion of exogenous genes without disrupting the host natural gene expression whilst simultaneously lowering the risk of silencing of the exogenous DNA. Such regions, known as "safe harbours" have been frequently used in human and mouse cell lines [158][159][160]. Identified safe harbour loci knowledge, coupled with efficient endonuclease-mediated targeted integration transformation protocols, can revolutionise genetic engineering strategies to produce recombinant biopharmaceuticals by circumventing reproducibility and stability issues associated with random chromosomal integration [161].…”
Section: Genetic Glyco-engineeringmentioning
confidence: 99%